Unilateral lung hypoplasia presenting in seventh decade of life: a rare case report - Chandra, Baishakhi; K., Bhaskar; G. K., Paramjyothi (International Journal of Advances in Medicine, 2018)
Pulmonary hypoplasia is a bronchopulmonary foregut anomaly in which gross morphology of the lung is preserved but there is decrease in the number or size of airways, vessels, and alveoli. Unilateral pulmonary hypoplasia is a rare clinical condition and most patients reported in the literature are newborns and infants, but patients may remain asymptomatic until late adolescent or till adulthood 65 years old male with parkinsonism was referred to our department with complaints of recent chest symptoms. Clinical examination revealed loss of lung volume in left hemithorax. CT scan thorax and bronchoscopy confirmed the diagnosis of left sided pulmonary hypoplasia. This case report highlights the possibility of pulmonary hypoplasia as one of the differential diagnoses in adult patients presenting with loss of lung volume and to the best of our knowledge he is the eldest patient so far reported.